P089 Constraints for Clinical Guideline Implementation In Mongolian Primary Health Care Facilities. (15th August 2013) - Sumberzul, N; Maximenco, E; Ouynbileg, S; Munkhtaivan, A; Jousilahti, P
Abstract : Background: The goal of the Millennium Challenge Account Mongolia (MCA-Mongolia) Health Project is to reduce morbidity and mortality due to Non-Communicable Diseases (NCD) through extensive training of health staff, development of clinical guidelines and provision of equipment and other material resources. Four clinical guidelines were developed within the framework of the project: hypertension, type 2 diabetes, and breast and cervical cancers. Objectives: Facility Based Impact Study (FBIS) in 2010 gathered information on the capacity of health facilities to provide NCD services prior the project, and to assess the quality of services. Multi-stage stratified (urban and rural) sampling was used to select 194 primary health care facilities, and 730 individual respondents - representing different health worker categories - were selected within the facilities. The quantity and quality of NCD related services were assessed based on five factors; (1) human resources, (2) NCD screening activities, (3) availability of standards and guidelines, (4) health education materials, and (5) equipment and supplies. Results: Only 10% of the facilities met the defined requirements for 'high quality' in the provision of NCD services, 38% met the level of 'middle quality', 28% of facilities met the 'minimum level', and 24% were classified as facilities not meeting basic requirements and categorised as below the minimum quality level. Conclusions: At least half of the health facilities need a marked improvement, and for one quarter the need is urgent. Insufficient training and time, and lack of materials were main barriers for effective NCD prevention and control.